Key miRNAs and Genes in the High-Altitude Adaptation of Tibetan Chickens - Chen, Binlong; Li, Diyan; Ran, Bo; Zhang, Pu; Wang, Tao (Frontiers in Veterinary Science, 2022)
Tibetan chickens living at high altitudes show speciﬁc physiological adaptations to the extreme environmental conditions. However, the regulated bases of how chickens adapt to high-altitude habitats remains largely unknown. Here, we sequenced 96 transcriptomes (including 48 miRNA and 48 mRNA transcriptomes of heart, liver, lung and brain) and resequenced 12 whole genomes of Tibetan chickens and Peng’xian Yellow chickens. We found that several miRNAs show the locally optimal plastic changes occurred in miRNAs of chickens, such as miR-10c-5p, miR-144-3p, miR-3536 and miR-499-5p. These miRNAs could have effects on early adaption of high-altitude environment of chickens. In addition, the genes under selection between Tibetan chicken and Peng’xian yellow chicken were mainly related to oxygen transport and oxidative stress. The I-kappa B kinase/NF-kappa B signalling pathway is widely found for high-altitude adaptation in Tibetan chickens. The candidate differentially expressed miRNAs and selected genes identiﬁed in this study, may be useful in current breeding efforts to develop improved breeds for the highlands.